Upaya Pasangan Suami Isteri Disabilitas Dalam Membentuk Keluarga Sakinah: - Nur Iskandar; M. Kholil Nawawi (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
The results of this research are couples with disabilities who are speechless in an effort to achieve Sakinah are the efforts made by a husband and wife with disabilities are trying to live in harmony, trying to give in, being patient and trusting, always grateful for what is produced, mutual understanding and understanding of the condition of the couple, trying to carry out religious obligations as well as possible. , trying to maintain good relations with family, community and neighbors, listening to parents' advice, trying to take part in community activities and recitations, working hand in hand in meeting household needs, trying to set an example by being a role model for children, especially in religious guidance. Constraints faced by speech-impaired married couples are difficult to find a dream job due to limitations in communication and education, family interference in domestic life, unable to fulfill all the wishes of their children and wives, emotional problems. jealous), less than optimal in providing guidance to children and wives. Based on the results of the analysis conducted by the author, it turns out that all respondents can be categorized into Sakinah II, namely families that are built on a legal marriage, have been able to meet their life needs, are able to understand the importance of implementing religious teachings and religious guidance in the family and are able to hold social interactions. religion with their environment, but have not been able to save. Keywords: Efforts, Couples with Disabilities, Sakinah.